Production and Modification of Cellulose Nanocrystals from Agave tequilana Weber Waste and Its Effect on the Melt Rheology of PLA - Soledad-Cecilia Pech-Cohuo; Gonzalo Canche-Escamilla; Alex Valadez-González; Victor Vladimir Amilcar Fernández-Escamilla; Jorge Uribe-Calderon (International Journal of Polymer Science)
The production and surface modification of cellulose nanocrystals (CNC) from Agave tequilana Weber waste (ATW) and their effect on the melt rheology of PLA were investigated. For that, CNC were obtained from ATW residues by acid hydrolysis and grafted with 2-ethyl hexyl acrylate (2-EHA) to promote compatibility with nonpolar polymers, such as PLA. The morphology of CNC occurred as rods, spheres, and the so-called porous network observed by scanning electron microscopy (SEM) and electron transmission microscopy (TEM), and the crystallinity of the cellulose fibers was ~73% and increased up to ~94% for CNC followed by X-ray diffraction (XRD). The acid hydrolysis and alkali extraction process produce changes on the native cellulose type I from ATW bagasse resulting in a mixture of cellulose type I and II and was preserved after CNC isolation and surface grafting. Polymer grafting was assessed using Fourier-transform infrared spectroscopy (FTIR) and X-ray electron spectroscopy (XPS). Upon surface modification, the grafted CNC presented better thermal stability than CNC pristine evaluated by thermogravimetric analysis (TGA), and the surface energy of the CNC was decreased which could promote CNC dispersion within polymers. Both pristine and surface modified CNC were melt mixed with PLA to produce nanocomposites at different concentrations of CNC. Dynamic time sweep tests showed that the introduction of CNC and CNC/2-EHA decreased the complex viscosity of PLA due to polymer degradation during compounding.